Culture in international development: the role of Concerts Norway in the India-Norway music cooperation (2002–2017). Issue 8 (16th November 2020) - Korum, Solveig; Subramaniam, Bindu
ABSTRACT: The article assesses how Concerts Norway has interacted with the Norwegian Ministry of Foreign Affairs and local musical actors in India to build infrastructure in the cultural field in India. Using ethnographic methods and document analysis, it finds that Concerts Norway successively shifted from rational, via entrepreneurial to relational brokerage, adapting the programme and development communication to shifting Ministry of Foreign Affairs policies and the Indian partner's needs. The article raises critical questions about arts development versus general views on development assistance, and highlights asymmetry between mainstream development models and the need to strengthen the art sector, towards its sustainability.